Autoantibodies Status in a Sample of Iraqi Celiac Disease Patients - Al Saffar, Jenan (Iraqi Journal of Science, 2023)
Fifty celiac disease (CD) patients (21 males and 29 females) with an age range of 2-35 years and 25 apparently healthy controls were investigated for 10 autoantibodies (anti-tissue transglutaminase IgA antibody; ATA, anti-tissue transglutaminase IgG antibody; ATG, anti-gliadine IgA antibody; AGA, anti-gliadine IgG antibody; AGG, anti-nuclear antibody; ANA, anti-double strand DNA antibody; AdsDNA, anti-thyroid peroxidase antibody; ATP, anti-phospholipid antibody; APP, anti-myeloperoxidase antibody; AMP and anti-proteinase 3 antibody; AP3) in their sera. Six autoantibodies (ATA, ATG, AGA, AGG, AMP and AP3) showed significant variations between CD patients and controls. The first four antibodies were not detected in sera of controls, while in patients, their percentage frequencies were 44.0, 22.0, 56 and 72.0%, respectively. With respect to AMP autoantibody, 36.0% of patient's sera were positive for this autoantibody; while in controls, the corresponding frequency was much lower (7.70%). AP3 autoantibody behaved in a similar manner, and its frequency was higher in patients compared to controls (46.0 vs. 19.2%).Autoantibody AGG recorded the highest sensitivity and specificity (76.0)(100.0) respectively.